MircoRNA-143-3p regulating ARL6 is involved in the cadmium-induced inhibition of osteogenic differentiation in human bone marrow mesenchymal stem cells. (1st October 2020) - Wu, Lu; Song, Jia; Xue, Junchao; Xiao, Tian; Wei, Qinzhi; Zhang, Ziji; Zhang, Yangcong; Li, Ziyin; Hu, Youkun; Zhang, Gaoqiang; Xia, Haibo; Li, Junjie; et al.
Graphical abstract: Highlights: Cadmium attenuates the osteogenesis of hBMSCs. Cadmium induced the blockage of ARL6 and Wnt/β-catenin pathway and the increase of miR-143-3p, which targeted ARL6 in hBMSCs. ARL6 is involved in the cadmium-induced blockage of the Wnt/β-catenin pathway and the suppression of osteogenesis by hBMSCs. miR-143-3p via ARL6 is involved in cadmium suppression of the Wnt/β-catenin pathway and osteogenic differentiation of hBMSCs. Abstract: Cadmium, which is extensively distributed in the environment, accumulates in organisms through the trophic chain. Although cadmium can cause bone injury, its role in osteogenesis of human bone marrow mesenchymal stem cells (hBMSCs) remains unclear. The present study investigated the effect of cadmium chloride (CdCl2 ) on osteogenesis of hBMSCs and the underlying mechanism. CdCl2 dose-dependently reduced the viability of hBMSCs. Concentrations of CdCl2 (2.5 and 5.0 μM) increased miR-143-3p levels; decreased levels of adenosine diphosphate-ribosylation factor-like protein 6 (ARL6); inhibited Wnt family member 3A (Wnt3a), β-catenin, lymphoid enhancer factor (LEF1), and T-cell factor 1 (TCF1); and suppressed osteogenesis of hBMSCs. Inhibition of miR-143-3p or overexpression of ARL6 with lentivirus blocked these CdCl2 -induced changes. Luciferase reporter assays confirmed that miR-143-3p binds to the 3'-UTR regions of ARL6 mRNA. Reduced-expression of miR-143-3p enhanced the CdCl2 -induced suppression of the osteogenesis of hBMSCs and inhibition of the Wnt/β-catenin pathway, effects that were reversed by down-regulated expression of ARL6. Thus, miR-143-3p targets ARL6 to down-regulate the Wnt/β-catenin pathway, which is involved in the suppression of osteogenic differentiation of hBMSCs. The results provide new directions for clinical treatment of bone diseases resulting from cadmium toxicity.